Morale and Job Satisfaction Levels among Teachers in Tanzania: A Case of Selected Public Secondary Schools in the Northern Zone - Ombeni W. Msuya (Selected Topics in Humanities and Social Sciences Vol. 2, 2021)
A case study on the role of extrinsic factors (hygiene factors) and socio-demographic factors in determining morale and job satisfaction among teachers in public secondary schools in Tanzania was undertaken. Biographical variables pertaining to teachers’ age, sex, marital status and work experience were investigated to determine whether they had any significant contribution on the level of morale and job satisfaction experienced. Morale and job satisfaction has been perceived differently by different researchers in the field of human resource and management. The study employed mixed methods of data collection including the use of instruments such as an interview guide, questionnaires and documentary review checklist. The study found that job satisfaction among teachers in public secondary schools northern Tanzania was not homogeneous; socio-economic and demographic factors had a great contribution on varying morale and job satisfaction levels. For example, female teachers’ job satisfaction was statistically significant (t(84) =2.62, p = 0.04), so was the job satisfaction of young teachers (bellow 40 years) (t(84) = -2.22, p = 0.01). However, age and working experience had a great contribution towards teachers’ job satisfaction and dissatisfaction. The study concludes that the socio-economic and demographic factors have potential strength in designing and sustaining job satisfaction model which accounts for morale and job satisfaction challenges among teachers in public secondary schools in Tanzania. The motivators and hygiene factors were confirmed to have great contribution on job satisfaction among teachers in public secondary schools in Tanzania.